2005
DOI: 10.1007/s11103-005-8105-8
|View full text |Cite
|
Sign up to set email alerts
|

Conservation and Divergence of FCA Function between Arabidopsis and Rice

Abstract: Although several genes have been identified in rice which are functionally equivalent to the flowering time genes in Arabidopsis, primarily genes involved in the photoperiod pathway, little data is available regarding the genes that function in the autonomous pathway in rice. In order to acquire further insight into the control of heading dates in rice, we isolated and conducted an expression analysis on OsFCA, which exhibited 38% sequence homology with Arabidopsis FCA. The N-terminal region of the OsFCA prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
54
2
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(61 citation statements)
references
References 65 publications
4
54
2
1
Order By: Relevance
“…PtFLC is regulated post-transcriptionally by alternative splicing Alternative splicing is a common regulatory mechanism of gene expression at posttranscriptional stage in eukaryotic organisms (Simpson and Filipowicz 1996;Lee et al 2005;Wang and Brendel 2006). Although several thousand plant genes were now known to produce multiple transcripts (Reddy 2001;Wang and Brendel 2006), the precise function of most splicing variants and their encoded proteins were not known, in Xowering plants, functional studies Fig.…”
Section: Discussionmentioning
confidence: 99%
“…PtFLC is regulated post-transcriptionally by alternative splicing Alternative splicing is a common regulatory mechanism of gene expression at posttranscriptional stage in eukaryotic organisms (Simpson and Filipowicz 1996;Lee et al 2005;Wang and Brendel 2006). Although several thousand plant genes were now known to produce multiple transcripts (Reddy 2001;Wang and Brendel 2006), the precise function of most splicing variants and their encoded proteins were not known, in Xowering plants, functional studies Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Extending this type of analysis to identify specific AS events that are conserved among multiple species will identify those "ancestral" candidate AS events that are more likely to be functionally significant. For example, one of the FCA gene AS events involved in flowering control (see above) is conserved between Arabidopsis and rice (Lee et al 2005). Computationally identifying conserved AS events requires the identification of robust cross-species orthologous gene sets.…”
Section: Evidence That Plant As Has a Biological Rolementioning
confidence: 99%
“…Previous studies have identified the genes controlling flowering time in rice (Shinozuka et al, 1999;Izawa et al, 2003;Doi et al, 2004;Lee et al, 2005;Lu et al, 2006;Kim et al, 2007;Tamaki et al, 2007). The DNA sequences of these genes in strain 9311 of indica and strain Nipponbare of japonica were acquired by a rice genome search in the National Center for Biotechnology Information (NCBI) (http://www.ncbi.nlm.nih.gov/), the BGI-RIS (http://rise.genomics.org.cn/rice/index2.jsp), and the GRAMENE (http://www.gramene.org/ genome_browser/index.html) databases.…”
Section: Nipponbare (O Sativa Japonica)mentioning
confidence: 99%
“…Eighteen flowering time-controlling genes were selected according to published references (Shinozuka et al, 1999;Izawa et al, 2003;Doi et al, 2004;Lee et al, 2005;Lu et al, 2006;Kim et al, 2007;Tamaki et al, 2007). The sequences of these genes in Nipponbare (japonica) and 9311 (indica) were acquired by a search of rice genome in public databases (NCBI, BGI-RIS, and GRAMENE) and were aligned using Vector NTI advance 10 (data not shown).…”
Section: Screening For Genes Controlling Flowering Timementioning
confidence: 99%